Merdeka Curriculum: Educational Communication for Learning Recovery - Yunidyawati Azlina (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This research aims to describe the Merdeka curriculum as a form of educational communication for the learning recovery period after the COVID-19 pandemic. This research is qualitative. The type of approach in this research is descriptive qualitative. The data in this research is secondary data in the form of scientific articles, documents related to research, and data from the internet. The technique used in this research is qualitative research with documentation study techniques / historical research or documentary study, namely searching for information related to the development of the research topic through news, official government documents, etc., which is then continued by compiling a bibliography of references related to the research. Research reviewed. This research indicates that the Merdeka curriculum is a form of educational communication for learning recovery. It is due to the gradual implementation of the Merdeka curriculum and the involvement of the social environment as a "learning space" by the nature of communication in general and educational communication in particular. It is a process with comprehensive interaction between the communication components involved.